Menghidupkan Lapangan Sepak Takraw: Upaya Meningkatkan Minat Olahraga di Kolok Nan Tuo - Anggun Permata Sari; Aisyah Fitri; Marsha Shalzabil; Muhammad Arya Fathiir; Abdul Aziz; Mulia Rahmat; Ferdi Agusrianto (Jurnal Kemitraan Masyarakat, 2025)
Interest in sepak takraw sports in Kolok Nan Tuo Village, Sawahlunto, has decreased significantly, especially among the younger generation. One factor that influences this is the lack of adequate facilities. This article highlights the importance of reviving the sepak takraw field in the village as a step to increase community interest in sports. Sepak takraw, as a traditional sport, has the potential to strengthen social relationships, improve discipline, and have a positive impact on physical and mental health. This article also discusses several efforts that can be made to revive the sepak takraw field, including community mutual cooperation, holding tournaments, and involving youth and community leaders. It is hoped that through these efforts, Kolok Nan Tuo Village can create a more active community in takraw sports. Reviving the sepak takraw field is not only about improving facilities, but also rebuilding the spirit of sports as an integral part of everyday life.